Technological consumption for technophiles and its consequences: analysis of the social networks and online videogames - Loayza, Jerjes (2018)
Our study is divided into three parts directly related to the arrival of new technologies and their impact in the socialization of the young. In the first part, a theoretical balance is made in order to elucidate the processes of writing and speech that converge in the virtual uses from today. In the second part, the consequences of the social networks in the last 5 years are analyzed from two types of social mediators: Messenger and Facebook. For this, the chat mechanisms are described, as a mode of interaction in real time, for the purpose of deepening the mode in which young people have been building news socialization ways through specialized codes. The growing distrust would provoke the migration towards a type of social network whose photographs and comments give some type of security, such as Facebook or Whatsapp. At the same time, it has been perceived that a proliferation of “no places” is taking place, as spaces of social isolation to keep alive said virtual fantasy.The third part deepens the analysis of videogames which since the past decade brought the possibility of playing connected to the internet in real time with other players in the world, allowing to surpass the geographic and cultural barriers. In this scenario, Latin America entered this process, even though we identify a certain degree of intolerance and stigmatization from users of developed countries, condemning them to the silence through the online violence they practice against them. On the other hand, the symbolic considerations released in these encounters and confrontations allow to recognize emotions and sensibilities found within the barrier of the virtual and the real, showing us a Latin-American scenario where the recognition quest meets the ideal  construction that surpasses the playful side, in order to join the socialization process of youths.